Coumarin precursor from Micromelum integerrimum leaves - Wong Phakhodee (2018)
Integerriminol (1), a coumarin precursor, was isolated from the leaves of Micromelum integerrimum along with 10 known coumarins and a flavonoid. Their structures were intensively elucidated on the basis of spectroscopic data including UV, IR, NMR, and TOF-HRMS and compared with those previously reported. A plausible biosynthetic pathway of coumarins derived from integerriminol (1) is also proposed.